2007
DOI: 10.1021/bi062233u
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure and Cell Selectivity of Piscidin 1 and Its Analogues,

Abstract: Piscidin 1 (Pis-1) is a novel cytotoxic peptide with a cationic alpha-helical structure that was isolated from the mast cells of hybrid striped bass [Silphaduang, U., and Noga, E. J. (2001) Nature 414, 268-269]. Pis-1 is not selective for bacterial versus mammalian cells. In the present study, to develop novel antibiotic peptides with selectivity for bacterial cells, we examined the effect of substituting two glycine residues, Gly8 and Gly13, with Ala or Pro on this peptide's structure and biological activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
90
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 92 publications
(105 citation statements)
references
References 49 publications
7
90
0
Order By: Relevance
“…We employed negatively charged LUVs composed of 1 : 1 (w/w) PC/PG lipids used for mimicking the major components of the cell membrane of bacteria. 17,18) The percentage of calcein leakage 2 min after exposure to ginsenosides or nisin was used to assess the ability to permeabilize the membrane. The results showed that 100 mg/ml of ginsenosides (at the MIC) induced 52.1% leakage of calcein from negatively charged vesicles, whereas 40 mg/ml of nisin (at the MIC) only induced approximately 10% of leakage of the dye (Fig.…”
Section: ) Resultsmentioning
confidence: 99%
“…We employed negatively charged LUVs composed of 1 : 1 (w/w) PC/PG lipids used for mimicking the major components of the cell membrane of bacteria. 17,18) The percentage of calcein leakage 2 min after exposure to ginsenosides or nisin was used to assess the ability to permeabilize the membrane. The results showed that 100 mg/ml of ginsenosides (at the MIC) induced 52.1% leakage of calcein from negatively charged vesicles, whereas 40 mg/ml of nisin (at the MIC) only induced approximately 10% of leakage of the dye (Fig.…”
Section: ) Resultsmentioning
confidence: 99%
“…Examples of piscidins are also dicentracin from the European bass (Dicentrarchus labrax) [165], chrysophsins from red sea bream (Chrysophrys major) [166], and epinecidin from the orange-spotted grouper (Epinephelus coioides) [167]. Lee et al [168] determined the solution structure of piscidin-1, and then piscidin-2 was found to cause cell membrane damage to three fungal strains known to cause infections in humans [169]. Piscidin-immunoreactive cells were most common at sites of pathogen entry (including the skin, gill, and gastrointestinal tract), and immunopositive cells were usually most consistent with mast cells [151].…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%
“…The peptide exhibits antimicrobial activity against methicillin-resistant Staphylococcus aureus (24), viruses such as HIV-1 (25), fungi (26), and cancer cells (27). Like other AMPs, piscidin induces dye leakage in model membranes and membrane disruption is proposed to be its primary mechanism of action against bacteria (28,29). The surfacebound structures of p1 were determined independently by ssNMR and all-atom molecular dynamics (MD) in two different bacterial cell mimics (30).…”
Section: Introductionmentioning
confidence: 99%